Augmenting the Out of Classroom Learning of Machine Drawing Laboratory Course - Shreeshail, M. L.; Koti, C. M. (Journal of Engineering Education Transformations, 2016)
Engineering drawing, traditionally termed as engineering graphics, has been the language of engineers. When it comes to mechanical engineering, this language gets elevated to a level fetching its status of first language in its domain. In engineering practices, any lapse in reading/interpreting drawings will be costly. The error in reading engineering drawings has been a worrying factor in the industries for engineering practitioners. There is a need for an immediate focus on the teaching-learning activity in this drawing course. This article reports an attempt to elevate the graphical communication skills in a class of 2nd year mechanical engineering students. The purpose of the study was to test the effectiveness of the ’out of classroom’ approach in improving the skill. The results show that the teaching approach is capable of enhancing the engineering drawing skills, and the approach has the potential to elevate the skill in one semester course of study. In the middle of our study, we attempted two more practices which are worth sharing. First practice was letting student recognize his/her own skill-level on the first class of the course and the skill-level achieved on the last class of the course and the second, psychological effect of quiz in assessing the learnt skills.